THE DEVELOPMENT OF SMOOTH PURSUIT EYE MOVEMENT WITH AUDITORY RHYTHMIC CUEING COMPUTER PROGRAM OF ADOLESCENT IN MODERATE POST-TRAUMATIC BRAIN INJURY - Thongsook, Pitark; Thepsatitporn, Sarawin; Kaewkaen, Pratchaya (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Objectives of research; 1) To develop smooth pursuit eye movement (SPEM) with auditory rhythmic cueing computer program of adolescence in moderate post-traumatic brain injury. 2) To examine the effects of the program. The quasi-experimental research using pretest - posttest control group design was used to examine the program. The subject were 44 people with moderate traumatic brain injury and selected according to the specified criteria. The subject divided into experimental and control group with 22 subjects in each group by simple random method. The control group received normal care and the experimental group were trained according to the developed program. This studying comprised of 2 phases: In the first phase, program was developed by applying Biased competition theory of selective attention by Desimone and Duncan, Feature-Integration theory of attention by Treisman and Gelade and premotor theory of attention. The second phase program was testing the implementation of the program. The instrument consists of screening research subject, The smooth pursuit eye movement (SPEM) with auditory rhythmic cueing computer program, The instruments used to measure dependent variables were the cued recall memory task and the program satisfaction assessment form. Data were analyzed by frequency, percentage, mean, standard deviation, and t-test. Major findings were as follows: 1) The developed program included four sessions. The SPEM level is directed at 40, 60, 80, and 100 times per minute during each session. The CVI (content validity index) ranged from .91 to 1.00. The program consisted of four 14-minute sessions number of 16 times. 2) After training with this program, the experimental group's accuracy of cued recall memory was significantly (p.001) higher than before training programs, and increased more than the control group. Conclusion: The smooth pursuit eye movement with auditory rhythmic cueing computer program of adolescence in moderate post-traumatic brain injury can improve cued recall memory in moderate post-traumatic brain injury patients and they are most effective when used on a daily basis.